The Main Properties of Diphtheriae Causative Microorganism Circulated in Postepidemic Period from Biofilm Culture - Kharseeva, G.G.; Frolova, J.N.; Gerasimov, V.N.; Gasretova, T.D. (International Journal of Pediatrics and Child Health, 2014)
Task – to study the main properties toxigenic strain of Corynebacterium diphtheriae circulated in postepidemic period from biofilm culture. It was shown that Diphtheriae causative agent has the ability to biofilm formation that is accompanied by exopolysaccharide matrix formation. This combines with changes of morphologic properties (decrease of bacteria sizes), cultures properties (decrease of colonies sizes, R-S-dissociation) and antibiotic susceptibility. The most effective towards Diphtheriae infection causative microorganism are cefotaxime, gentamycin, linkomycin, kanamycin and cefazolin, because they have no changes in susceptibility of Corynebacterium diphtheria? in the biofilm structure.